Faust and Job: The Dual Facets of Happiness - Elias L. Khalil (20518877) (2025)
This paper advances two interrelated theses. As for the first thesis, it distinguishes well-being, on the one hand, from happiness, on the other hand. As for the second thesis, it differentiates between two important facets of happiness: what this paper calls “happiness-as-tranquility” and “happiness-as-aspiration”. Actually, in order to differentiate the two facets of happiness, we first need to distinguish happiness from well-being. This is the case because happiness, after all, is a by-product of reflecting upon and ruminating over well-being. Given it is the same well-being, how could it give rise to different facets of happiness? It can only do so if we stop conflating happiness with well-being. This entails taking to task the widely accepted concept of “subjective wellbeing”. Such concept is expressly designed to obfuscate the difference between well-being and happiness. As for the two facets of happiness (the second thesis), this paper relies upon the contrast of two famous works of literature: the story of Job and the story of Faust. The contrast uncovers the criticality of the temporal dimension in the acts of reflection upon and rumination over well-being. If people reflect on past accomplishments, they experience backward-looking happiness along the Job story—i.e., happiness-as-tranquility. If people reflect on desire, they experience forward-looking happiness along the Faust story—i.e., happiness-as-aspiration. While the two facets of happiness seem contradictory, they are indeed complementary if we recognize the temporal element when one reflects upon and ruminates over well-being. Other Information Published in: Philosophies License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://www.mdpi.com/2409-9287/10/4/75